2022
DOI: 10.1186/s13018-022-03190-6
|View full text |Cite
|
Sign up to set email alerts
|

A case-driven hypothesis for multi-stage crack growth mechanism in fourth-generation ceramic head fracture

Abstract: Background Ceramic bearings are used in total hip arthroplasty due to their excellent wear behaviour and biocompatibility. The major concern related to their use is material brittleness, which significantly impacts on the risk of fracture of ceramic components. Fracture toughness improvement has contributed to the decrease in fracture rate, at least of the prosthetic head. However, the root cause behind these rare events is not fully understood. This study evaluated head fracture occurrence in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
5
0
3
Order By: Relevance
“…Postoperative complications, short and long-term clinical outcomes, PROMs and QALYs, the efficacy of specific implants, comparison of different surgical techniques and survival analyses were among the main outcome of the published studies. The “Register of Orthopaedic Prosthetic Implant (RIPO) of Emilia-Romagna region” published 30 papers from 2002 to 2022 [ 24 , 645 ]. Among them, twenty-eight were cohort studies [ 24 , 26 , 39 , 43 , 57 , 145 , 164 , 189 , 231 , 288 , 297 , 482 , 491 , 502 , 506 , 508 , 527 , 540 , 562 , 563 , 569 , 585 , 592 , 597 , 599 , 624 , 630 , 645 ], one was RCT [ 476 ] and one registry protocol [ 468 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative complications, short and long-term clinical outcomes, PROMs and QALYs, the efficacy of specific implants, comparison of different surgical techniques and survival analyses were among the main outcome of the published studies. The “Register of Orthopaedic Prosthetic Implant (RIPO) of Emilia-Romagna region” published 30 papers from 2002 to 2022 [ 24 , 645 ]. Among them, twenty-eight were cohort studies [ 24 , 26 , 39 , 43 , 57 , 145 , 164 , 189 , 231 , 288 , 297 , 482 , 491 , 502 , 506 , 508 , 527 , 540 , 562 , 563 , 569 , 585 , 592 , 597 , 599 , 624 , 630 , 645 ], one was RCT [ 476 ] and one registry protocol [ 468 ].…”
Section: Resultsmentioning
confidence: 99%
“…The “Register of Orthopaedic Prosthetic Implant (RIPO) of Emilia-Romagna region” published 30 papers from 2002 to 2022 [ 24 , 645 ]. Among them, twenty-eight were cohort studies [ 24 , 26 , 39 , 43 , 57 , 145 , 164 , 189 , 231 , 288 , 297 , 482 , 491 , 502 , 506 , 508 , 527 , 540 , 562 , 563 , 569 , 585 , 592 , 597 , 599 , 624 , 630 , 645 ], one was RCT [ 476 ] and one registry protocol [ 468 ]. Of these 30 studies, 16 were survival [ 26 , 164 , 189 , 231 , 288 , 482 , 491 , 502 , 508 , 527 , 540 , 563 , 569 , 585 , 592 , 599 ], six analysed implant types [ 24 , 43 , 297 , 506 , 624 , 645 ], and two studied postoperative complications [ 597 , 630 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improper impaction of the femoral head prosthesis during surgery has also been identified as a potential risk factor for ceramic head fracture ( 43 ). Although the use of fourth-generation ceramics significantly improves the material's resilience, making it less prone to brittle fracture, orthopedic surgeons still need to pay attention to obtaining proper head seating on a clean taper during femoral head assembly as a prerequisite to reduce the risk of any damage occurring at the head-taper junction ( 44 ). The surgeon's clinical experience and expertise play a crucial role in ensuring the success of the surgery and the safety of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Our second patient had experienced sudden-onset pain without an obvious trigger or trauma. Lucchini et al ( 44 ) demonstrated that ceramic head fracture can occur even without complications or significant previous trauma. Slight micromotion can lead to interface damage, leading to the loosening of the ceramic head and ultimately resulting in ceramic femoral head fracture.…”
Section: Discussionmentioning
confidence: 99%